17 alpha‐hydroxylase deficiency: A case report of young Chinese woman with a rare gene mutation. Issue 7 (25th July 2022) - Han, Li Hui; Wang, Liang; Wu, Xiu Yun
Abstract: We report a young adult woman with 17 alpha‐hydroxylase deficiency (17α‐OHD) in Shandong province of China. The patient carried compound heterozygous mutations in the CYP17A1 gene: c.985–987 delinsAA (p.Tyr329LysfsX90) and c.1486C > T (p.Arg496Cys). The patient's hypertension and hypokalemia were resolved after taking medications of glucocorticoid, aldactone, and calcium antagonists. Abstract : We report a young adult woman with 17 alpha‐hydroxylase deficiency (17α‐OHD) in Shandong province of China. The patient carried compound heterozygous mutations in the CYP17A1 gene: c.985–987 delinsAA (p.Tyr329LysfsX90) and c.1486C>T (p.Arg496Cys).